Time dependence in joint replacement to multi-products grouped. The case of hospital food service. Issue 1 (31st December 2016) - Rojas, Fernando
Abstract : This paper proposes a stochastic inventory policy of periodic review with joint replacement for multi-products applicable to food service. The products to supply are grouped by multivariate cluster analysis by features of interest in this service. The associated inventory model that describes the random demand for each product considers forecast temporal dependence through a generalized linear autoregressive moving average (GLARMA) model. Optimization of the cost function related to the inventory model is obtained considering the expected value of the forecast of demand per unit time and stochastic programming. The proposed policy is exemplified with real-world data from a Chilean food service hospital.